Research on Ziziphus Mauritiana: Bibliometric Studies - Tg Ainul Farha Tg Abdul Rahman; Khairina Idris; Najla Qaisara Shariman; Nurdalila A’wani Abdul Aziz (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani